The cognitive processes preceding an organizational innovation: Implications for emerging economy contexts (Los procesos cognitivos que anteceden la innovación organizacional: implicaciones para contextos de economías emergentes) - Lira Arjona, Alfonso López (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. In hyper competitive environments, knowledge has turned to be the most valuable resource. However, a competitive advantage is achieved through the firm’s capability for assimilating and exploiting it with commercial purposes, as a product or process innovation. Therefore, the cognitive processes, defined as knowledge creation, transfer, and assimilation preceding an organizational innovation, are critical for a firm’s survival in markets such as those of emerging economies. In addition, contextual factors such as the structure, the culture, strategic processes and information technologies have been identified in several studies as responsible for an effective knowledge transfer, while the effects of knowledge characteristics and the capabilities of senders and receivers have not been sufficiently integrated in literature. This study presents a literature review about the cognitive processes preceding an organizational innovation in order to map the different topics and research lines related to the phenomena. Then, the effects of contextual organizational factors, as found on different frameworks, are discussed. Finally, a proposed framework for application in emerging economies is introduced.